Smokeless Tobacco Consumption and Oral Cancer: A Case-Control Study (Journal of Preventive and Social Medicine, 2025)
Background: Smokeless tobacco consumption leads to oral cancer, which is a substantial source of morbidity and mortality in Bangladesh. This study was conducted to determine the association between smokeless tobacco consumption and the risk of oral cancer. Methods: It was a case-control study. Participants with oral cancer were considered cases, while those without oral cancer were regarded as controls. Data were collected through face-to-face interviews and reviews of the medical records through a pretested semi-structured questionnaire and checklist. Results: Tobacco consumption was significantly (p